Higher mathematics textbook - Konev, V. V. mathematician Associate Professor of Tomsk Polytechnic University, Candidate of Physics and Mathematics 1951- (TPU Publishing House, 2020)
The textbook consists of 7 chapters, each of which concentrates on a topic of Differential and Integral Calculus. The important concepts of Calculus are explained and illustrated by figures and examples. The textbook can be helpful for students who want to understand and be able to use standard differentiation and integration techniques, make numerical approximations, analyze the behavior of a function, operate with complex numbers, solve ordinary differential equations, and so on. The textbook is prepared at the Department of Higher Mathematics. It covers the topics to be studied in the second semester and it is intended for students who have been studied the basic Mathematics.